Survei Lingkungan Belajar (Sulingjar) Sekolah Dasar Ditinjau dari Perspektif Teori Belajar Behaviorisme Edward Lee Thorndike - Hardhita, Rizki Septa; Rahman, Fatchur; Luswandari, Wulan Fatikhah; Slamet, Slamet; Anggraini, Ade Eka (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
This study aims to understand the "Learning Environment Survey (Sulingjar)" program launched by the Ministry of Education and Culture of the Republic of Indonesia which is carried out in order to fulfill the National Assessment (AN) in the perspective of Edward Lee Thorndike's behaviorism learning theory. In the perspective of Thorndike's behaviorist learning theory, learning is the interaction between stimuli (stimulus) and responses (responses). There are similarities between what was proclaimed by the Minister of Education and Culture in the National Assessment and the concept of Thorndike's behaviorism learning theory. The writing of this article uses qualitative research with a type of descriptive approach. Data collection is carried out by observation, document review and literature study. The results of the study obtained the results of a good learning environment survey (distilljar) in elementary schools from the perspective of Edward Lee Thorndike's behaviorism learning theory about stimulus-response showed that the school safety climate, diversity climate, and good learning quality can increase student learning motivation..